2015
DOI: 10.1142/s2339547815400038
|View full text |Cite
|
Sign up to set email alerts
|

BioLEGO — a web-based application for biorefinery design and evaluation of serial biomass fermentation

Abstract: The composition of feedstock biomass and the selection of fermenting microorganisms are critical factors in biorefinery design. Feedstock biomass composition is constrained by local supply materials, but microorganism selection affords considerable flexibility. Once biomass feedstock is identified, biorefinery designers need to select optimal fermenting organisms. While fermentation by microorganism communities can increase the range of digested biomass compounds and can be more resistant to infections, it has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…This methodology enables the prediction of organism growth rates, as well as the prediction of minimal and maximal production rates of various metabolic compounds, based only on reaction stoichiometry and directionality. FBA-based approaches have a wide range of applications, including phenotype analysis, bioengineering and metabolic model reconstructions36373839.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology enables the prediction of organism growth rates, as well as the prediction of minimal and maximal production rates of various metabolic compounds, based only on reaction stoichiometry and directionality. FBA-based approaches have a wide range of applications, including phenotype analysis, bioengineering and metabolic model reconstructions36373839.…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, to predict the biofuel molecule production rates, we utilized one-step simulation framework described in previous work39 with metabolic models of S. cerevisiae 41 (original and modified to incorporate Xylose uptake, simulating RN1016 strain), of E. coli 42 and of C. acetobutylicum 43. The composition of the Ulva biomass was based on literature121344 and appears in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Serial fermentation is a design approach that offers tighter and more predictable control of inter-organism relations and reactions, thus enabling better process optimization [15][16][17][18]. Briefly, in this process each organism is grown separately.…”
Section: Introductionmentioning
confidence: 99%
“…In previous work we introduced BioLego-a platform that simulates the efficiency of biomass fermentation in two-step processes [15,16,19]. This current work leverages Microsoft Azure Cloud to enhance the BioLego framework and to allow high-scale simulations, exploring a large multiplicity of scenarios, of the efficiency of biomass fermentation in two-step processes.…”
Section: Introductionmentioning
confidence: 99%
“…We decided to focus on these molecules as they are the major carbohydrates in the Ulva species. In addition, in our previous work, we showed that the glucose, rhamnose and xylose contents of U. fasciata predict the potential of this feedstock for bioethanol fermentation (Vitkin et al 2015). In addition to examining the potential use of reflectance spectroscopy for deriving different sugar contents, we developed PLS to predict the contents of specific monosaccharides based on whole thalli spectrum features.…”
Section: Introductionmentioning
confidence: 99%